IEEE International Conference on Dielectric Liquids, 2005. ICDL 2005.
DOI: 10.1109/icdl.2005.1490111
|View full text |Cite
|
Sign up to set email alerts
|

Kerr electro-optic measurement of electric field distribution in rapeseed ester oil and pressboard composite system

Abstract: In oil-immersed power transformers, an insulating oil / pressboard (PB) composite insulation system is generally applied. In order to make power transformers more compact, it is necessary to optimize the insulation design with considering the charge behavior in liquid dielectrics. In addition, environment-friendly insulating oil for transformers is being interested. In this paper, we directly measured the electric field in parallel-plane electrodes and rapeseed ester oil / PB composite insulation system under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In previous research conducted by the authors of this article, the Kerr constant of transformer oil under ambient temperature conditions was determined to be 2.3 × 10 −15 m V −2 [26]. Correspondingly, empirical data obtained by other scholars have indicated that the Kerr constant of transformer oil at ambient temperatures typically falls within the range of approximately 2.0 × 10 −15 -4.5 × 10 −15 m V −2 [27][28][29]. Temperature dependence curves for B and E m were obtained, as shown in figure 8.…”
Section: Temperaturementioning
confidence: 58%
“…In previous research conducted by the authors of this article, the Kerr constant of transformer oil under ambient temperature conditions was determined to be 2.3 × 10 −15 m V −2 [26]. Correspondingly, empirical data obtained by other scholars have indicated that the Kerr constant of transformer oil at ambient temperatures typically falls within the range of approximately 2.0 × 10 −15 -4.5 × 10 −15 m V −2 [27][28][29]. Temperature dependence curves for B and E m were obtained, as shown in figure 8.…”
Section: Temperaturementioning
confidence: 58%
“…Decay time of space charge on mineral oil/pressboard interface was studied in [6] by using pulsed electroacoustic technique, where dissipation of 90% charges takes about 2 hours. Time constants of rapeseed oil/pressboard and mineral oil/pressboard insulation systems were compared in [7] with the help of Kerr electro-optic measurement, where it was found that it is only several seconds for rapeseed oil/pressboard insulation system but several thousand seconds for mineral oil/pressboard insulation system. The explanation of the difference given is due to the much lower volume resistivity of rapeseed oil than the mineral oil.…”
Section: A Possible Reasons For Accumulative Effectmentioning
confidence: 99%
“…Since it is very difficult to directly measure the space charge distribution in liquids, the space charge distribution is calculated from the electric field distribution measured using some optical methods in general. [1][2][3][4][5][6] Therefore, in order to obtain the space charge distribution at time intervals of millisecond, the measurement of the electric field distribution at time intervals of millisecond is required.…”
mentioning
confidence: 99%